Dietry Protein And Energy Requirements Of Meat Type Japanese quail For Growth - Narayanankutty K (Department of Poultry Science, College of Veterinary Science, 1987)
A three square factorial experiment designed to study the dietary requirments of protein and energy for meat type Japanese quail (Coturnix coturnix japonica) for growth, under the hot-humid conditions of Kerala is presented in this thesis.